2022
DOI: 10.3390/rs14143425
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Classification of Floating Plastic Litter Using a Vessel-Mounted Video Camera and Deep Learning

Abstract: Marine plastic pollution is a major environmental concern, with significant ecological, economic, public health and aesthetic consequences. Despite this, the quantity and distribution of marine plastics is poorly understood. Better understanding of the global abundance and distribution of marine plastic debris is vital for global mitigation and policy. Remote sensing methods could provide substantial data to overcome this issue. However, developments have been hampered by the limited availability of in situ da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The correlation between the camera-identified large pieces of litter (>50 cm) and the trawl results was high, and the correlation with the trawl results for small pieces of litter (<5 cm) was directly proportional to the size of the litter. Similarly, Armitage et al [48] used the same algorithm to monitor the drifting litter in the south-western bays of the United Kingdom, and the results showed that the accuracy of the identification of the plastic litter was as high as 95.2%, and the accuracy of the classification of the plastic litter was 68%.…”
Section: Mobile Monitoring On Boardmentioning
confidence: 99%
“…The correlation between the camera-identified large pieces of litter (>50 cm) and the trawl results was high, and the correlation with the trawl results for small pieces of litter (<5 cm) was directly proportional to the size of the litter. Similarly, Armitage et al [48] used the same algorithm to monitor the drifting litter in the south-western bays of the United Kingdom, and the results showed that the accuracy of the identification of the plastic litter was as high as 95.2%, and the accuracy of the classification of the plastic litter was 68%.…”
Section: Mobile Monitoring On Boardmentioning
confidence: 99%
“…Video cameras and images have also been used for the detection and recognition of plastics based on the objects' shape and colour [18][19][20][21]. Colour images were used together with SVM and YOLOv5 networks for detection and classification of plastics with accuracies of 94.7% and 95.2%, respectively [22,23]. These methods showed to be accurate; however, they focused mainly on the recognition of plastic bottles.…”
Section: Related Workmentioning
confidence: 99%
“…The Plastic (Polystyrene) category is the first category most found on the sandy beaches of Ainoshima Island. Since the mass production of consumer plastic products began in the 1950s (Armitage et al, 2022), plastic waste has reached the natural environment, accounting for 60-80% of marine debris globally.…”
Section: The Most Common Litter Category Is Found On Ainoshima Islandmentioning
confidence: 99%